Over-pumping of groundwater in Irbid governorate, northern Jordan: a conceptual model to analyze the effects of urbanization and agricultural activities on groundwater levels and salinity - Odeh, T; Mohammad, A; Hussein, H; Ismail, M; Almomani, T (Springer Nature, 2019)
The governorate of Irbid has the highest population density in Jordan and most of its water demand is supplied by groundwater. Both natural population growth and waves of migrations increased the number of its inhabitants during the last 40 years. This population growth has increased: the amount of land covered by urban and agricultural development over this time period; and the groundwater demand by 227% due to increasing of drinking water demand, urban water usage and for agricultural irrigation. As a result of the continuous pumping, groundwater levels have decreased by about 70 m and the salinity of pumped groundwater has increased by about 1000 µS/cm in some areas. A conceptual model to account for the observed changes in groundwater levels and salinity has been developed through an integrated approach of remote sensing and geographic information systems.